The correspondence between Ricardo Palma and Nicolás de Piérola - Kapsoli Escudero, Wilfredo (2019)
The fifty-seven letters and three chronicles that Ricardo Palma wrote to President Nicolás de Piérola allow us to understand some essential aspects during the War with Chile, such as: the patriotism of the people of Lima, the looting of the National Library, the marginalization towards the indigenous population and the nationalism of Andrés Avelino Cáceres.